Abd Al-Rahman Ibn Khaldun (732-808AH/1332-1406CE) - Akhmetova, Elmira (Pelanduk Publications Sdn. Bhd., 2018)
This chapter elaborates on the life, ideas, philosophy and contributions of Ibn Khaldun to modern civilisation as a builder of Islamic civilisation